Comparison of FIR Window Filter Variation Results on Pink Noise Audio - John Christopher; Nabila Husna Shabrina; Cindy Cornelia; Yoel Zakhary (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
IIR and FIR filters are the most used digital signal filters. The application of each filter type depends on the needs of the user. IIR filters are generally used for applications with limited memory. In comparison, FIR filters are usually used for applications where the linear phase is essential. In this study, the implementation of FIR filters on pink noise audio samples was observed. Various FIR window method filters such as rectangular, hamming, hanning, and Blackman will be compared. Each type of filter will have a different filter order due to computing the frequency cut-off point for each filter. The comparisons were made by observing the gain response, the time domain signal, the frequency response, and the phase response. The results indicated that the Hanning window method is a better filter because it produces low delay and good attenuation. Things to be considered in designing FIR filters are fluctuations in frequency response and phase shift. Alterations on cut-off points on the filters and delay usage can be deployed for some improvement